A Cross-Sectional Survey Study Among Panchakarma Practitioners on the Practices of Nasya Karma with Gokarna (AYUSHDHARA, 2025)
Nasya karma (medication through the nasal route) is one of the Panchakarma in which medicine is delivered through the nose for various purposes, which include eliminating excess Doshas (regulatory functional factors of the body) or pacifying them. This study explored the various practices of Nasya karma with Gokarna (a hand-held instrument that can hold a small amount of liquid) among Panchakarma practitioners. A descriptive cross-sectional survey was conducted in the form of a self-administered questionnaire containing 28 questions through Google forms among 125 Panchakarma practitioners of India. The questionnaire was validated and pretested before being circulated. A total of 125 Panchakarma practitioners participated in the survey. Considering some of the usage conveniences, 107 of 125 participants raised the requirement for an innovative device for Marsha Nasya to overcome the ambiguities. The study could provide some valuable insights into the current practices and detailed perspectives of Panchakarma practitioners regarding the practices of Nasya Karma with Gokarna. The findings shed some light on the scope of future research on a device that incorporates modern technology to ensure precise temperature control, accurate dosage measurement, hygienic application and controlled delivery, aligning with the principles of Ayurveda.